Analysis and development of the ProTrack application: construction timeline management using Extreme Programming Methodology - Denny Jean Cross Sihombing (Institute of Computer Science (IOCS), 2023)
The Evaluation and Adaptation phase in developing the ProTrack application using the Extreme Programming (XP) Method reflects the adaptive approach's success in ensuring the application's quality and relevance as it evolves. The research method involved a structured survey to gather feedback from users and stakeholders, involving 45 respondents from construction company employees. The survey results showed that 78% of the respondents found significant benefits in managing projects through the app's features. Furthermore, the performance and security evaluation process through thorough testing resulted in an 18% decrease in application response time and a 12% increase in data security. The app successfully improved its performance and integrity through cyber risk prevention measures and code optimization. An essential contribution of this research is seen in the successful development and testing of the ProTrack application with XP's adaptive approach to construction project management. The research results provide valuable insights for developers and practitioners in technology and project management, particularly in the face of the complex dynamics of the construction industry. The research generated a deeper understanding of user perceptions and needs by relying on survey feedback data, enabling continuous application improvement. The research confirmed the effectiveness of the XP-based adaptive approach in producing a responsive and effective application solution capable of adapting to rapid changes in the dynamic construction project environment.